The epigenetic modifier Fam208a is required to maintain epiblast cell fitness - Bhargava, Shohag; Cox, Brian; Polydorou, Christiana; Gresakova, Veronika; Korinek, Vladimir; Strnad, Hynek; Sedlacek, Radislav; Epp, Trevor Allan; Chawengsaksophak, Kallayanee (Scientific reports, 2017)
Gastrulation initiates with the formation of the primitive streak, during which, cells of the epiblast delaminate to form the mesoderm and definitive endoderm. At this stage, the pluripotent cell population of the epiblast undergoes very rapid proliferation and extensive epigenetic programming. Here we show that Fam208a, a new epigenetic modifier, is essential for early post-implantation development. We show that Fam208a mutation leads to impaired primitive streak elongation and delayed epithelial-to-mesenchymal transition. Fam208a mutant epiblasts had increased expression of p53 pathway genes as well as several pluripotency-associated long non-coding RNAs. Fam208a mutants exhibited an increase in p53-driven apoptosis and complete removal of p53 could partially rescue their gastrulation block. This data demonstrates a new in vivo function of Fam208a in maintaining epiblast fitness, establishing it as an important factor at the onset of gastrulation when cells are exiting pluripotency.
Keywords: mutace; Animals; Nuclear Proteins; epigeneze genetická; apoptóza; epitelo-mezenchymální tranzice; zvířata; Mice; Primitive Streak; Mutation; zárodečné listy; jaderné proteiny; primitivní proužek; Germ Layers; Epigenesis, Genetic; Apoptosis; Epithelial-Mesenchymal Transition; myši